MODEL SUPERVISI KOLABORATIF DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK GURU: STUDI KASUS PADA SEKOLAH DENGAN RENDAHNYA HASIL BELAJAR SISWA - Rismayani, Risha; Rori Dolayance; Sufyarma; Rifma; Tia Ayu Ningrum (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the implementation of a collaborative supervision model in improving teachers’ pedagogical competence in schools with low student learning outcomes. The study is motivated by the persistent issue of low student achievement, which is closely related to teachers’ limited pedagogical skills and the ineffective implementation of traditional supervision practices. This research aims to analyze how collaborative supervision contributes to improving teaching quality and student outcomes. A qualitative approach with a case study design was employed. Data were collected through classroom observations, in-depth interviews, and document analysis involving school principals and teachers. The findings reveal that collaborative supervision, implemented through stages of planning, implementation, and reflection, significantly enhances teachers’ pedagogical competence. Quantitative indicators from previous studies show improvements in teacher competence scores from low to high categories across supervision cycles. Furthermore, the study found that improved teaching practices lead to increased student participation, motivation, and academic achievement. Collaborative supervision fosters a reflective and collegial culture among teachers, promoting continuous professional development. In conclusion, the collaborative supervision model is an effective strategy for improving both teacher competence and student learning outcomes, particularly in schools facing academic challenges.